Unsteady three dimensional flow of couple stress fluid over a stretching surface with chemical reaction - Hayat, Tasawar; Awais, Muhammad; Safdar, Ambreen; Hendi, Awatif A. A. (Nonlinear Analysis: Modelling and Control, 2012)
The unsteady three-dimensional flow of couple stress fluid over a stretched surface is investigated. Analysis has been performed in the presence of mass transfer and chemical reaction. Nonlinear flow analysis is computed by a homotopic approach. Plots are presented and analyzed for the various parameters of interest. A comparative study with existing solutions in a limiting sense is made.
Keywords: mass transfer effects; nonlinear analysis; couple stress fluid